Implementation of Management Information Systems in Educational Institutions Public Vocational School 8 Samarinda - Akhmad Ramli; Subiantoro; Fina Kholij Zukhrufin; Sudadi Sudadi (Tarbiyah Departement collaboration with AMCA, 2023)
Management Information System is a system designed to provide information to support decision-making on management activities (planning, implementing, organising and controlling) within an organisation. Understanding management information systems based on information technology, including understanding the concept of information systems, information use, and the value of information. System boundaries have been determined by encouraging the quality of the system's work. The work process in each system produces a continuous result (output) and an evaluation system through feedback treatment. The sense is that if the output contains information contrary to the organisation's achievements, it will become input in the system. If the system has received the results of the feedback, the system will make the necessary revisions and adjustments so that the output is consistent with its original purpose. Then with the rapid advancement of technology, The ability of an educator must be able to tame technology so that they can become slaves or tools, not enslaved by technology. This research aims to identify Islamic education management information systems and their concepts and implementation processes in Islamic educational institutions. The research results are: Implementation of existing information systems in schools, and the community feels the output of the implementation of the information system. Data collection techniques used in this study were observation and interviews with related educational institutions.